Circulating Antibodies Against Common Cold Coronaviruses Do Not Interfere with Immune Responses to Primary or Booster SARS-CoV-2 mRNA Vaccines - Bindu Adhikari; Eugene M. Oltz; Richard J. Gumina; Maryssa K. Kick; Linda J. Saif; Anastasia N. Vlasova (Vaccines)
Background: Pre-existing cross-reactive antibodies (Abs) against common cold coronaviruses (CCCoVs) have been hypothesized to influence the immune responses to SARS-CoV-2 vaccine-induced Ab responses. Methods: Serum samples from healthy healthcare workers (HCWs, n = 64) receiving mRNA vaccines were collected at seven time points: pre-COVID-19-vaccination (Pre), post-first dose (Vax1), post-second dose (Vax2), and 6-, 9-, 12-, and 15-months post-Vax2. Booster vaccine doses (n = 23) were received 1–80 days prior to the 9 m sample collection time point. We used peptide-based enzyme-linked immunosorbent assays (ELISAs) to measure SARS-CoV-2/CCCoV-specific IgG/IgA/IgM and SARS-CoV-2 IgG4 (associated with immune tolerance) Ab levels in the HCW serum samples. Additionally, we measured Epstein–Barr/influenza A (unrelated pathogens) virus-specific IgG Ab levels. Results: We observed that vaccination significantly increased SARS-CoV-2 IgG Ab levels at the Vax1 (p ≤ 0.0001) and Vax2 (p ≤ 0.0001) time points compared to Pre-Vax. These Ab levels declined at 6 months post-vaccination but increased again following the booster vaccine dose around the 9-month post-Vax2 time point in a cohort (n = 23) of the HCWs. However, this increase was modest compared to those induced by the primary vaccine series. Interestingly, a moderate but continuous increase in SARS-CoV-2 S IgG4 Ab levels was observed throughout this study, becoming statistically significant by the 15-month time point (p = 0.03). Further, a significant increase in CCCoV IgG (but not IgA/IgM) Ab levels was observed at the Vax1 time point, suggestive of cross-reactive or non-specific immune responses. Finally, we observed no negative correlation between the levels of pre-existing CCCoV-specific Abs and the vaccine-induced Ab response (Vax1/Vax2). Conclusions: Pre-existing CCCoV Abs do not interfere with the development of vaccine-induced immunity. However, vaccine-associated Abs wane over time, which may be associated with the increasing IgG4 Ab response.